Training and Workshop Implementation of Group Counseling with Expressive Therapy Techniques for The Prevention of Students Sexual Harassment in Junior High School 16 Padang - Syahniar Syahniar; Firman Firman; Puji Gusri Handayani (Universitas Negeri Padang, 2019)
The training and workshop activities are carried out based on the phenomenon of the many problems that have arisen in the global era with sophisticated and modern technology today, one of the events experienced by many junior high school students is sexual harassment both physically and verbally. For this reason, counselors and counselors must make various counseling and counseling services, one of which is group guidance services, including efforts to prevent sexual harassment among students. Group counseling services can be done with a variety of approaches, one of which is the approach and techniques of expressive therapy counseling. The expressive therapist believes that individuals are different in expressing what is in themselves, there are individuals who are more open to express what is felt in him, including communicating the anxiety he feels. The results show that there is an increase in understanding and knowledge of school counselors / school counselors, especially in terms of implementing counseling in schools. During this time in school, counseling teachers carry out counseling with traditional methods, namely asking with special techniques, but after this training the counseling teacher can conduct counseling with an expressive therapy approach.